Growth and Lipidomic Analyses of Penaeus monodon Larvae Supplemented With Aurantiochytrium limacinum BCC52274 - Visudtiphole, Virak; Khudet, Jutatip; Chaitongsakul, Panomkorn; Plaisen, Siwat; Siriwattano, Jittima; Laiphrom, Seansook; Klaysuban, Anupong; Raweeratanapong, Thaninthorn; Sittikankaew, Kanchana; Rattanaphan, Nakul; Koichai, Looksorn; Unagul, Panida; et al. (Frontiers in Marine Science, 2021)
Long-chain polyunsaturated fatty acids (LC-PUFAs) are essential for growth and health of larval marine animals. Marine animals have a limited capability for LC-PUFA synthesis, and the larvae must obtain LC-PUFAs from diet. The protist Aurantiochytrium limacinum (AL) is abundant in 22:6 n-3 (docosahexaenoic acid, DHA), 22:5 n-3 (docosapentaenoic acid, DPA) and 16:0 fatty acids, which qualifies it as an LC-PUFA source for feed application. Therefore, in this study, a common feed containing lower amounts of total LC-PUFAs, Thalasiosira weissflogii, was replaced with AL at graded proportions and supplied to Penaeus monodon larvae from mysis (M) 1 to post-larval (PL) 2 stages to supplement LC-PUFAs in the diet. After that, all shrimp from PL2 to PL12 were continuously reared and subjected to the same diet regime, which was a combination of Artemia and commercial dried feed. The AL-supplemented PL2 shrimp demonstrated marked accumulation of the key fatty acids present in AL—16:0, DPA and DHA. The supplemented larvae showed no difference in growth during the supplementation period from M1 to PL2; however, average body weight and biomass were increased in PL12 shrimp that were fed earlier with AL. Lipidomic analysis revealed that profiles of fatty acids but not lipid classes/subclasses in PL shrimp reflected the supplied diet. The main saturated fatty acid (SFA, 16:0) predominantly accumulated in acylglycerols, which are energy-reserve lipids, in PL2 shrimp. Both LC-PUFAs (DHA and DPA) were preferentially deposited in phospholipids or structural lipids. Furthermore, while the amounts of both LC-PUFAs increased along with the amount of supplied AL, that of the SFA did not. This suggests that LC-PUFAs were prioritized to be stored over SFA when both types of fatty acids were present in high amounts. This analysis substantiates the importance of LC-PUFAs and provides an insight into how different types of the dietary fatty acids were differentially accumulated in lipid classes and subclasses for their biological functions.